Distribution and status of Turdus thrushes in white-sand areas of eastern Colombia, with a new subspecies of T. leucomelas - Stiles, F. Gary; Avendaño, Jorge Enrique (Zootaxa, 2019)
White-sand areas in the Colombian Amazon harbor many endemic and specialist species that are relatively little studied with respect to their ecology, distribution and zoogeographic affinities, for example Turdus thrushes. A recent expedition to the Serranía de Chiribiquete, a mountain range of Guianan origin in the Colombian Amazon, resulted in the discovery of an enigmatic Turdus thrush restricted to white-sand vegetation. Molecular phylogenetic analyses of the ND2 gene revealed that this population is genetically similar to T. leucomelas albiventer, from which it differs in its smaller size and darker, duller plumage. Therefore, we here describe this population as a new subspecies of T. leucomelas. Furthermore, our inspection of specimens of Turdus taxa from eastern Colombia revealed the existence of sympatry between T. ignobilis debilis and T. i. arthuri at two sites. Based on this evidence and previously documented genetic and phenotypic differences, we recognize T. arthuri as a distinct biological species. We analyze distributions and measurements of functional traits among four thrush taxa of eastern Colombia.